THE BEGINNING INVESTOR IN THE CAPITAL MARKET AND INVESTMENT PRODUCTS - VĂDUVA CECILIA ELENA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Investment management focuses on achieving financial goals, not necessarily beating market performance. The main challenge is managing risks and ensuring consistent income, which may be more important than maximizing profits. Investment is a complex process that involves specialized knowledge. The absence of this knowledge can lead to ineffective evaluations and financial losses, with customers at risk of buying inappropriate or high-risk products. Following some basic principles in this area can make it easy for anyone to become an investor. In order to become a better investor, it is essential that one learns to manage risks and returns, select an appropriate capital allocation, diversify one's portfolio, maximize one's investments, protect against inflation and constantly monitor their evolution .